Assessing gender and ethnic differences in developmental trajectories of offending - Ferrante, Anna (Sage, 2013)
Research on diversity in offending patterns is crucial given ongoing polemical debates concerning the relationship between gender, ethnicity and crime. Competing theoretical perspectives, limited supporting evidence and inconclusive or contradictory findings from prior research point to the need for more empirically-grounded, generalizable research which compares and contrasts offending patterns across and within gender and ethnic groups. The current study applies a semi-parametric group-based modelling approach to a large, longitudinal dataset of offenders to determine if, and how, offending trajectories vary across gender and ethnic sub-groups. Findings suggest that some trajectory attributes (e.g. number and shape) are shared across gender/ethnic groups, while other trajectory attributes (height, peak age) are not. An exploratory investigation of the risk factors associated with trajectory group membership finds that few of the available factors discriminate between trajectories either within or across gender/ethnic offender groups. The findings fill a knowledge gap, particularly in relation to offending patterns in Australia. Invariance in trajectory risk factors present a challenge to taxonomic theories of offending.